An Update on Adverse Cutaneous Drug Reactions in HIV/AIDS - Koraisha Hoosen; Anisa Mosam; Ncoza Cordelia Dlova; Wayne Grayson (MDPI AG, 2019)
Background: The global mortality from HIV and the cutaneous burden of infective, inflammatory and malignant diseases in the setting of AIDS have significantly declined following the advent of highly active antiretroviral therapy. Regrettably, there has been a contemporaneous escalation in the incidence of adverse cutaneous drug reactions (ACDR), with studies attesting that HIV-positive individuals are a hundred times more susceptible to drug reactions than the general population, and advanced immunodeficiency portending an even greater risk. Several variables are accountable for this amplified risk in HIV. Summary: Adverse reactions to trimethoprim-sulfamethoxazole are the most common, increasing from approximately 2-8% in the general population over to 43% amongst HIV-positive individuals to approximately 69% in subjects with AIDS. Antituberculosis drugs and antiretrovirals are also well-known instigators of ACDR. Cutaneous reactions range from mild morbilliform eruptions to severe, life-threatening manifestations in the form of Stevens-Johnson syndrome/toxic epidermal necrolysis. Histological features vary from vacuolar interface changes to full-thickness epidermal necrosis with subepidermal blister formation. A precipitous diagnosis of the ACDR, clinically and histologically if necessary, together with the isolation of the causative drug is critical. The identification process, however, is often complex and multifaceted due to polypharmacy and inconclusive data on which drugs are the most likely offending agents, especially against the background of tuberculosis co-infection. Key Messages: Whilst milder cutaneous reactions are treated symptomatically, severe reactions mandate immediate treatment discontinuation without rechallenge. Further studies are required to establish safe rechallenge guidelines in resource-limited settings with a high HIV and tuberculosis prevalence.